Consensus for experimental design in electromyography (CEDE) project: Terminology matrix. (August 2021) - McManus, Lara; Lowery, Madeleine; Merletti, Roberto; Søgaard, Karen; Besomi, Manuela; Clancy, Edward A.; van Dieën, Jaap H.; Hug, François; Wrigley, Tim; Besier, Thor; Carson, Richard G.; Disselhorst-Klug, Catherine; et al.
Abstract: Consensus on the definition of common terms in electromyography (EMG) research promotes consistency in the EMG literature and facilitates the integration of research across the field. This paper presents a matrix developed within the Consensus for Experimental Design in Electromyography (CEDE) project, providing definitions for terms used in the EMG literature. The definitions for physiological and technical terms that are common in EMG research are included in two tables, with key information on each definition provided in a comment section. A brief outline of some basic principles for recording and analyzing EMG is included in an appendix, to provide researchers new to EMG with background and context for understanding the definitions of physiological and technical terms. This terminology matrix can be used as a reference to aid researchers new to EMG in reviewing the EMG literature.